Predicting weight category-specific performance zones for Olympic, world, and european weightlifting competitions - Chavda, S.; Comfort, P.; Lake, J. P.; Bishop, C.; Turner, A. N. (The Journal of Strength and Conditioning Research, 2023)
Understanding the total likely required weight category to achieve a specific rank within a specific competition can aid in the long-term and short-term preparation and tactics for performance teams. The primary objective of this investigation was to develop a set of predictive models for new weight categories across 5 performance zones for 3 major weightlifting competitions. Performance total (Ptot) data for top 15 male athletes were obtained from the International Weightlifting Federation website from 1998 to 2020 across the Olympics, and World and European Championships. A second-order polynomial regression was conducted with 95% confidence, and predictive intervals were calculated. The average of the newly contested body mass was then used as the intercept. Predictions were compared against current performances of the new weight categories up to the 2020 Olympics. Results revealed that the models for all competition types varied in their predictive ability for each performance zone, across each new weight category. On average, predicted Ptot displayed a difference from actual Ptot of 3.65 ± 2.51% (12.46 ± 9.16 kg), 0.78 ± 3.29% (2.26 ± 10.08 kg), and -1.13 ± 3.46% (-4.32 ± 11.10 kg) for the Olympics, and World and European Championships, respectively. The results suggest that the predictive models may be a good indicator of future performances; however, the models may have greater efficacy in some weight categories and performance zones than others.